Isolation And Characterization Of Phosphate Solving Bacteria From Swamp Soil With High Levels Of Acidity - Galang Indra Jaya,; Hidayah Utami, Sri Nuryani; Widada, Jaka; Annisa Yusuf, Wahida; Abbas, Saipul; Fatturahman Ridwan, Nur; Noviyanto, Amir (Jurnal Pertanian, 2023)
Phosphate solubilizing bacteria (PSB) are one of the microbes that play an important role in soil and plant cycles. Phosphate (P) is a very important macronutrient for plants. In soil, most of the P element is found to be unavailable to plants because it is fixed by Ca, Al or Fe. This research aims to identify BPF in acid soil which has the potential to dissolve phosphate elements. The method used in this research is the isolation of BPF from acid soil using the National Botanical Research Institute's Phosphate (NBRIP) medium, phosphate dissolution index test and UV Visual. Soils from overflow type C (TLC) swamps have higher diversity compared to TLB soils. The abundance of BPF in TLC soil was higher (5,4 107 CFU per gram) compared to soil from overflow zone B (TLB) (2,9 107 CFU per gram) because TLC soil had a lower acidity level than TLB. There were 55 BPF isolates obtained from these two types of soil. Two isolates (TLB1 and TLB2) had a better phosphate solubilization index and all potential isolates that were extracted and subjected to gDNA amplification showed a DNA band at 1330-1500 bp.